Designation and psychometric properties of the Short Form Postpartum Quality of Life Questionnaire (SF-PQOL): an application of multidimensional item response theory and genetic algorithm - Fariba Nikan; Mohammad Asghari Jafarabadi; Sakineh Mohammad-Al; Mojgan Mirghafourvand (Tabriz University of Medical Sciences, 2018)
Background: Utilizing multidimensional item response theory (MIRT) and genetic algorithm(GA) we aimed to design and test the psychometric properties of the short form Postpartum Quality of Life Questionnaire (PQOL). Methods: In this methodological study, 500 women aged 18 to 42 were enrolled through multistage random sampling scheme in Tabriz, Iran. We used MIRT model and GA to identify a short form of the 40-item PQOL measure (SF-PQOL). Construct and criterion validity of theSF-PQOL was assessed by confirmatory factor analysis (CFA) and the correlation between SFPQOL scores with a 12-item short form of QOL (SF-12) and Edinburgh Postnatal Depression Scale (EPDS) scores, respectively. The internal consistency, test-retest reliability and feasibility of the measure were evaluated. Results: sixteen- and 13-item SF-PQOL were identified based on MIRT and GA, respectively.The results indicate the better performance of the MIRT based 13-item SF-PQOL; Construct and criterion validity, the test-retest and internal consistency reliability, and the feasibility were confirmed in the MIRT based SF-PQOL, but not in the GA-based SF-PQOL. Conclusion: The MIRT suggests a 13-item SF-PQOL with adequate content which demonstrated satisfactory validity, reliability, and feasibility. SF-PQOL could be used across the population for both research and clinical objectives.